Chronic exposure to a gambling-like schedule of reward predictive stimuli can promote sensitization to amphetamine in rats - Zack, Martin; Zack, Martin; Featherstone, Robert E.; Mathewson, Sarah; Fletcher, Paul J. (Frontiers in Behavioral Neuroscience, 2014)
Addiction is considered to be a brain disease caused by chronic exposure to drugs. Sensitization of brain dopamine (DA) systems partly mediates this effect. Pathological gambling (PG) is considered to be a behavioral addiction. Therefore, PG may be caused by chronic exposure to gambling. Identifying a gambling-induced sensitization of DA systems would support this possibility. Gambling rewards evoke DA release. One episode of slot machine play shifts the DA response from reward delivery to onset of cues (spinning reels) for reward, in line with temporal difference learning principles. Thus, conditioned stimuli (CS) play a key role in DA responses to gambling. In primates, DA response to a CS is strongest when reward probability is 50%. Under this schedule the CS elicits an expectancy of reward but provides no information about whether it will occur on a given trial. During gambling, a 50% schedule should elicit maximal DA release. This closely matches reward frequency (46%) on a commercial slot machine. DA release can contribute to sensitization, especially for amphetamine. Chronic exposure to a CS that predicts reward 50% of the time could mimic this effect. We tested this hypothesis in 3 studies with rats. Animals received 15 x 45-min exposures to a CS that predicted reward with a probability of 0, 25, 50, 75 or 100%. The CS was a light; the reward was a 10% sucrose solution. After training, rats received a sensitizing regimen of 5 separate doses (1 mg/kg) of d-amphetamine. Lastly they received a 0.5 or 1 mg/kg amphetamine challenge prior to a 90-min locomotor activity test. In all 3 studies the 50% group displayed greater activity than the other groups in response to both challenge doses. Effect sizes were modest but consistent, as reflected by a significant group x rank association ( = .986, p = .025). Chronic exposure to a gambling-like schedule of reward predictive stimuli can promote sensitization to amphetamine much like exposure to amphetamine itself.